Blood-derived mitochondrial DNA copy number is associated with gene expression across multiple tissues and is predictive for incident neurodegenerative disease - Yang, Stephanie Y.; Castellani, Christina A.; Longchamps, Ryan J.; Pillalamarri, Vamsee K.; O'Rourke, Brian; Guallar, Eliseo; Arking, Dan E. (Genome Research, 2021)
Mitochondrial DNA copy number (mtDNA-CN) is a proxy for mitochondrial function and is associated with aging-related diseases. However, it is unclear how mtDNA-CN measured in blood can reflect diseases that primarily manifest in other tissues. Using the Genotype-Tissue Expression Project, we interrogated relationships between mtDNA-CN measured in whole blood and gene expression from whole blood and 47 additional tissues in 419 individuals. mtDNA-CN was significantly associated with expression of 700 genes in whole blood, including nuclear genes required for mtDNA replication. Significant enrichment was observed for splicing and ubiquitin-mediated proteolysis pathways, as well as target genes for the mitochondrial transcription factor NRF1. In nonblood tissues, there were more significantly associated genes than expected in 30 tissues, suggesting that global gene expression in those tissues is correlated with blood-derived mtDNA-CN. Neurodegenerative disease pathways were significantly associated in multiple tissues, and in an independent data set, the UK Biobank, we observed that higher mtDNA-CN was significantly associated with lower rates of both prevalent (OR = 0.89, CI = 0.83; 0.96) and incident neurodegenerative disease (HR = 0.95, 95% CI = 0.91;0.98). The observation that mtDNA-CN measured in blood is associated with gene expression in other tissues suggests that blood-derived mtDNA-CN can reflect metabolic health across multiple tissues. Identification of key pathways including splicing, RNA binding, and catalysis reinforces the importance of mitochondria in maintaining cellular homeostasis. Finally, validation of the role of mtDNA CN in neurodegenerative disease in a large independent cohort study solidifies the link between blood-derived mtDNA-CN, altered gene expression in multiple tissues, and aging-related disease.